The Antidiabetic Drug Lobeglitazone Protects Mice From Lipogenesis-Induced Liver Injury via Mechanistic Target of Rapamycin Complex 1 Inhibition - Lee, Yu Seol; Park, Jeong Su; Lee, Da Hyun; Lee, Dong-Kyu; Kwon, Sung Won; Lee, Byung-Wan; Bae, Soo Han (Frontiers in Endocrinology, 2018)
Nonalcoholic fatty liver disease (NAFLD) is a metabolic disorder closely linked with type II diabetes (T2D). The progression of NAFLD is associated with the induction of lipogenesis through hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) pathway. An increase in lipogenesis induces endoplasmic reticulum (ER) stress and accelerates oxidative liver injury in the pathogenesis of NAFLD. Lobeglitazone, one of thiazolidinedione (TZDs), is used as an antidiabetic drug to lower serum glucose level through an increase in insulin sensitivity. It is known to improve pathological symptoms in animals and humans with NAFLD. However, the underlying molecular mechanism of the protective effects of lobeglitazone against NAFLD has not been elucidated. Here, we show that under the physiological condition of acute lipogenesis, lobeglitazone inhibits hepatic lipid synthesis, the subsequent ER stress, and ω-oxidation of fatty acids by inhibiting the mTORC1 pathway. As a result, lobeglitazone protected mice from lipogenesis-induced oxidative liver injury. Taken together, lobeglitazone might be a suitable drug for the treatment of patients with diabetes and NAFLD.